LEGAL POLICY ON ECO-PARTNERSHIPS TO ACHIEVE SUSTAINABLE DEVELOPMENT - Absori Absori; Mohammad Indra Bangsawan; Arief Budiono; Hari Sutra Disemadi (Diponegoro Law Review, 2022)
There is a lack of maximum realization of sustainable development in the Surakarta City Government’s partnerships. This study proposes a fishbone diagram that seeks the root causes that affect the realization of partnerships that encourage sustainable development in Surakarta. The study aimed to convey ideas on environment-based local government partnership policies (Eco-Partnerships) to achieve sustainable development. It was a descriptive, doctrinal-method legal research. The primary data was sourced from library research, and the author also carried out some field research. The research used several indicators, namely Surakarta City Government’s Partners, Regulations, and Culture as the small bones and the analysis result of the failure to realize eco-friendly partnerships as the big bone. The result of the study showed that the implementation status of 19 out of 52 regional partners and five regional partners with a focus on environmental activities had not yet been followed up by the regional government. The regulation was ineffective because the Surakarta Government lacked adequate policies on eco-partnerships. Therefore, the Surakarta City Government needed to enforce a policy based on regional regulations on partnerships that integrate economic, social, and environmental aspects (Eco-Partnership).